Application of a proposal for measurement of performance of a quality management system - Silveira, Orlando Ferreira da; Michelin, Claudia de Freitas; Siluk, Julio Cezar Mairesse (Revista de Administração da UFSM, 2017)
Currently in the corporate world growing focus by the speed that process changes, driven by frequent technological innovations, the performance of the economy and the strong competition established in its market. In this way, the incessant search for continuous improvement in organizations demands the implementation of systemic and measurable management systems, as a means to reduce vulnerability in relation to the impact caused by competitive forces. The present work, developed in two companies of the food industry, The Coca-Cola Company and Heineken Brazil, aims to verify the application and the contributions of a proposal of performance measurement of a quality management system, aiming to facilitate and Guide the measurement and analysis of the process of continuous improvement and the sustainability of organizational performance. Methodologically, a mapping and diagnosis was carried out to carry out a case study. Thus, it can be stated that the tool developed and its simulation contributed to the proactive, integrated and continuous measurement of the process of analysis of the implementation, improvement and performance of the quality management system, demonstrating the percentage of non-conformity of 1.01% for this system.